Yoga in daily life - "Joshi, K S" (New Delhi, 1985)
Every person must be self trained in maintaining their body in perfectly sound health, by keeping it physically active, mentally at peace and protected from environmental influences. This book comes forth as an ideal guide in this respect, presenting methodically illustrated details of Yogic practice, proper nutrition, and meditation etc. It is in clear and simple language. The book, completely true to the authentic tradition of classical yoga, is designed to meet the needs of our modern times. It is a holistic system of health, encompassing the science of the body, mind and soul.
Keywords: Yoga